Hydrosedimentology of the Paraguay River in the Corumbá fluvial reach, Pantanal wetland - Macedo, Hudson de Azevedo; Stevaux, José Cândido; Silva, Aguinaldo; Merino, Eder Renato; Lo, Edward Limin; Assine, Mario Luis (Revista Brasileira de Geomorfologia, 2019)
The Pantanal wetland is a complex landscape with distinct hydrogeomorphic compartments, with singular and hydrosedimentary processes. Examining these processes draws great interest in understanding Pantanal dynamics for both the management of the system and the geological record predicted by facies models. Hydrosedimentary data in the Pantanal remain scarce, in spite of government efforts to improve and increase data collection in the Upper Paraguay Basin. This study aims to enhance the understanding of active hydrosedimentary processes in the Pantanal Paraguay trunk-river system in the Corumbá reach. Hydrosedimentary surveys were accomplished in the main channel and tributaries of the Paraguay River. These surveys helped characterize the hydrosedimentary dynamics to consider the active sedimentary processes in this reach. The Paraguay River interacts complexly with its floodplain, which functions as a reservoir retaining flood water and disturbing river discharge. Bathymetric surveying showed that Paraguay River channel has longitudinal compound bar bedforms built by superimposition of ripples. The backwater effect, possibly related with both hydrological regime and geomorphological characteristics of the area, was detected by means of rating-curve analysis of the gauge stations. This effect is hydrologically produced by the out-of-phase flood pulse of the Pantanal and geomorphically driven by the hydraulic bottleneck of the Urucum and Bodoquena massifs. Both factors possibly occur simultaneously. The hydrogeomorphic characteristics (morphology, river competence, and stream power) of the Paraguay River denote that the elaboration of models more appropriate to the Pantanal context is needed.